2022
DOI: 10.1111/hex.13581
|View full text |Cite
|
Sign up to set email alerts
|

‘It Makes You Sit Back and Think Where You Wanna Go’: Veteran experiences in virtual whole health peer‐led groups

Abstract: Background: The Veterans Health Administration (VHA) is building a Whole Health system of care that aspires to empower and equip each Veteran to pursue a personally meaningful vision of health and well-being. As part of this effort, VHA has developed Taking Charge of My Life and Health (TCMLH), a peer-led, group-based programme that seeks to support Veterans in setting and pursuing health and wellbeing goals. Prior research showed TCMLH groups to positively impact Veteran outcomes; yet, little is known about V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…However, as one interviewee stated peer interactions should not act to prevent or delay interaction with the community, rather it should act to enable the journey. There is a growing body of research regarding peer led service provision in both the veteran and civilian population (Cheney et al, 2016 ; Shaw et al, 2021 ; Anderson et al, 2022 ; Gettings et al, 2022 ). Although such peer interventions hold great value there is a lack of research into their effectiveness (Ahern et al, 2015 ; Derefinko et al, 2018 ).…”
Section: Discussion and Implications For Clinical Settingsmentioning
confidence: 99%
“…However, as one interviewee stated peer interactions should not act to prevent or delay interaction with the community, rather it should act to enable the journey. There is a growing body of research regarding peer led service provision in both the veteran and civilian population (Cheney et al, 2016 ; Shaw et al, 2021 ; Anderson et al, 2022 ; Gettings et al, 2022 ). Although such peer interventions hold great value there is a lack of research into their effectiveness (Ahern et al, 2015 ; Derefinko et al, 2018 ).…”
Section: Discussion and Implications For Clinical Settingsmentioning
confidence: 99%
“…Whole health programs can consist of wellness groups with a peer facilitator, one-on-one personal coaching, health education opportunities, and complementary and alternative medicine modalities. Regarding groups with facilitators, 15 veterans participating in a peer-led, groupbased, whole health program, Taking Charge of My Life and Health (TCMLH), were interviewed, and the findings indicated positive experiences of internalizing the value of health engagement, making healthy lifestyle changes, forging social connections, and taking on an active role in health care (Anderson et al, 2022). Additionally, Abadi et al (2022) found positive gains after a nine-week, 90-minute, TCMLH program in self-care attitudes and behaviors, motivation, meaning and purpose, mental health, stress, progress towards goals, and goalspecific hope using program evaluation surveys in 77 veterans.…”
Section: Introductionmentioning
confidence: 99%